PEMIKIRAN PLURALISME KH. ABDURRAHMAN WAHID DALAM MEMBANGUN TOLERANSI (1999-2001) - Oktarianda, Yoga (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research is about KH. Abdurrahman Wahid’s pluralism tough in building tolerance from 1999 to 2001. The purpose of this research is to find out the pluralistic thinking of KH. Abdurrahman Wahid in attitude towards diversity in society like religion, views, race, nation, culture and other differences from one human to another. The fight KH. Abdurrahman Wahid in establish pluralism is not just a discourse and theory but also at the level of practice which is reflected in his policies and actions. However, in reality, he often creates controversy and got a lot criticism from various circles, even though he continues to campaign for pluralism until the end of his life, in the name of building tolerance. This study uses a library research method with a historical - philosophical approach. The result of this research is in Indonesia pluralism is still a sensitive discourse and controversy. For those who are pro, pluralism is an inevetablity tfrom Allah SWT. Therefore, pluralism must be accepted and become a necessity. Meanwhile, for those who are contra, pluralism is understood as misguided understanding because teaches all religions is same and true. In this case KH. Abdurrahman Wahid became one of the figures who was pro against pluralism. For KH. Abdurrahman Wahid pluralism is not a negative concept. Pluralism is in line with Islamic values, Pancasila and also the state constitution. For him, pluralism is a fact and is a necessity because of the primordial differences between humans into various religions, races, ethnicities, nations, languages which cannot be avoided and all must be treated equally in all dimensions of national and state. Pluralism of KH. Abdurrahman Wahid divided into three things; Justice, freedom of religion, and freedom of thought or opinion freedom as a human right. In their efforts to uphold pluralism in society, they often got pros and contras. Many agree and there are also many who disagree. Therefore, he has received many obstacles from various groups or organization, including the Majelis Ulama Indonesia (MUI) which states that Pluralism is haram because it considers all religions to be the same. Keywords : Political thought, Pluralism, Tolerance